Tsunamis in the Japan Major: Shifting Tides and Resilience - Emi Otsuji; Luke Sharp (PORTAL: Journal of Multidisciplinary International Studies)
This reflective piece on the Japan Major at the University of Technology Sydney (UTS) marks three decades of the Bachelor of Arts in International Studies (BAIS), now the Bachelor of International Studies (BIS) since 2022. The past 15 years have been especially transformative for the Japan Major, shaped by two significant events: the devastating tsunami on 11 March 2011 and the declaration of a global pandemic on 11 March 2020. Remarkably connected by a single date, these events frame a reflection on resilience, adaptability, and the evolving practices of global education, with student experiences at the forefront. Using the word ‘tsunami’ both literally and metaphorically, this essay explores how such shifts challenge and inspire pedagogical approaches.